Handbook of structural stability. - Gerard, George (Technical note (United States. National Advisory Committee for Aeronautics), 1957)
A generalized crippling analysis for short monolithic panels with formed or extruded stiffeners is presented. The analysis applies to monolithic panels. Criteria are given for rivete panels which indicate if the panels can be considered to behave in a monolithic manner. Riveted panels that are subject to interrivet buckling and wrinkling or forced crippling do not behave in this manner. Methods are presented for estimating the strength of such panels.